Highly homologous simian T-cell leukemia virus type 1 genome in Japanese macaques: a large cohort study - Hiraga, Kou; Kitamura, Tomoya; Kuramitsu, Madoka; Murata, Megumi; Tezuka, Kenta; Okuma, Kazu; Hamaguchi, Isao; Akari, Hirofumi; Mizukami, Takuo (Virology journal, 2024)
Simian T-cell leukemia virus type 1 (STLV-1) is a retrovirus closely related to human T-cell leukemia virus type 1 (HTLV-1), the causative agent of adult T-cell leukemia (ATL). It has been shown that Japanese macaques (Macaca fuscata, JMs) are one of the main hosts of STLV-1 and that a high percentage of JMs (up to 60%) are infected with STLV-1; however, the molecular epidemiology of STLV-1 in JMs has not been examined. In this study, we analyzed full-length STLV-1 genome sequences obtained from 5 independent troops including a total of 68 JMs. The overall nucleotide heterogeneity was 4.7%, and the heterogeneity among the troops was 2.1%, irrespective of the formation of distinct subclusters in each troop. Moreover, the heterogeneity within each troop was extremely low (>99% genome homology) compared with cases of STLV-1 in African non-human primates as well as humans. It was previously reported that frequent G-to-A single-nucleotide variants (SNVs) occur in HTLV-1 proviral genomes in both ATL patients and HTLV-1 carriers, and that a G-to-A hypermutation is associated with the cellular antiviral restriction factor, Apobec3G. Surprisingly, these SNVs were scarcely observed in the STLV-1 genomes in JMs. Taken together, these results indicate that STLV-1 genomes in JMs are highly homologous, at least in part due to the lack of Apobec3G-dependent G-to-A hypermutation.